Analysis of Fisheries Business Development in order to Increase Gross Regional Domestic Product in Sukabumi City, West Java - Tuti Gantini; Euis Dasipah; Gijanto Purbo Suseno; Nunung Sondari; Acep Yusup (RIRAI Publisher, 2022)
The purpose of this study is to analyze the potential fisheries sub-sector to be developed in order to increase GRDP, in Sukabumi, West Java. Secondary data were obtained from BPS and related agencies, then analyzed using Local Quotient (LQ), Klasen Typology, and linear regression. The results showed that the order of potential to be developed was the ornamental fish cultivation sector, the second was the fishery product processing sector, the third was the fish hatchery sector and the fourth was the fish rearing sector. Based on the LQ value, the fishery product processing sector is the base sector with a source of raw materials for capture and freshwater aquaculture. The results of the regression analysis show that all fisheries sub-sectors contribute to regional income, starting from hatcheries, rearing, processing and production of ornamental fish